Soil nutrients, properties and carbon stock comparison between native and non-native ecosystems in Þingvellir, Iceland - María Svavarsdóttir 1970- (2018)
The five factors of soil formation are bedrock, climate, time, topography and biota. Vegetation affects soil development by organic matter input. It has been demonstrated worldwide that coniferous species are known to change the properties of soil, e.g. acidification, however this remains unproven in Iceland. Juniperus communis is the only native coniferous species in Iceland and it does not form forests. Over the past decades, non-native coniferous species have been introduced to Iceland and are still used in commercial forestry. Presently, the Icelandic Forest Service and local forestry associations in Iceland plant over 50% of coniferous species in new plantations. The purpose of this study is to compare vegetation coverage, plant species composition and live biomass, and various soil properties including pH, organic matter, available N-species, phosphorus, carbon stock, carbon and nitrogen percentages, C/N ratio and cation exchange capacity between different vegetation communities (spruce plantation, native birch forest and native heathland). Five study sites at each ecotype were located within Þingvellir National Park on a 10,000-year-old lava field and they share the same environmental conditions. This study identified significant soil acidification in the spruce plantation as well as higher organic matter, carbon, and nitrogen percentages. However, the spruce plantation had less species richness in the understory in comparison with the birch forest, which had more grass species and coverage and the heathland, which had more herbaceous species. Both heath and birch forest had full vegetation coverage in the understory but the spruce had only partial coverage. The live biomass was lowest in the spruce forest and highest in birch forest. In cation exchange capacity, a clear trend emerged where spruce had the lowest Ca2+ cation concentrations but highest Al3+ ion concentrations, indicative of a trend towards acidification. Spruce had the highest total CEC (TCEC) but the lowest base saturation (BS) and base ...